Sweated work, weak bodies : anti-sweatshop campaigns and languages of labor - Bender, Daniel E. (Rutgers University Press, 2004)
Sweated Work, Weak Bodies is the first book on the origins of sweatshops, exploring how they came to represent the dangers of industrialization and the perils of immigration.